A Cross-Sectional Epidemiological Survey of Work-Related Musculoskeletal Disorders and Analysis of Its Influencing Factors among Coal Mine Workers in Xinjiang. (10th August 2020) - Yong, Xianting; Li, Fuye; Ge, Hua; Sun, Xuemei; Ma, Xiaofan; Liu, Jiwen
Abstract : This study is to investigate the prevalence of work-related musculoskeletal disorders (MSDs) and the influencing factors among coal mine workers employed in on-site operations. The job burnout scale and MSD scale were implemented to investigate a random sample of 1, 500 coal mine workers working in on-site operations in Xinjiang, China. In total, 1, 325 valid questionnaires were collected, with a recovery rate of 88.33% (1, 325/1, 500). The rate of job burnout was 90%, of which 39.8% were categorized as mild burnout, 43.8% as moderate burnout, and 6.4% as severe burnout; the average job burnout score was 50.77 ± 11.93 . The annual prevalence of MSDs was 65.6%, with the highest annual prevalence in the waist (50.7%), followed by the neck, shoulder, and knee, and the lowest prevalence in the elbow (18.8%). Of the areas of the body affected by work-related MSDs, the highest proportion of requests for leave of absence was related to the waist, accounting for 25.7% of requests, while the lowest proportion (13.4%) was related to the wrist. In addition, the incidence of MSDs increased with the years of service. The lowest incidence of MSDs was associated with the two-shift and three-group working pattern. The prevalence of MSDs in the neck and waist was higher in women than in men. The prevalence of MSDs in various body parts increased with the years of service. Moreover, multiple logistic regression indicated that three shifts with four groups (OR = 1.096, 95% CI: 0.832-1.445), working more than 10 years (OR = 3.396, 95% CI: 2.369-5.748), working more than 20 years (OR = 3.008, 95% CI: 1.419-6.337), significant bending (OR = 2.062, 95% CI: 1.400-3.038), forward neck tilting (OR = 1.572, 95% CI: 1.071-2.281), maximum force operation within a short period of time (OR = 1.7222, 95% CI: 1.164-2.547), repeated movement of upper arms or fingers (OR = 1.495, 95% CI: 1.034-2.161), slip or fall incidents (OR = 1.124, 95% CI: 1.039-1.216), work under conditions of cold or temperature variations (OR = 1.911, 95% CI: 1.342-2.720), mild burnout (OR = 1.492, 95% CI: 1.016-2.191), moderate burnout (OR = 1.852, 95% CI: 1.267-2.708), and severe burnout (OR = 2.001, 95% CI: 1.145-3.496) were risk factors for MSDs. In conclusion, there is a high annual prevalence of MSDs among the coal mine workers employed in on-site operations in Xinjiang, China. Measures to reduce this prevalence are required.